ANALISIS STRUKTUR TEKS CERITA FANTASI PADA SISWA SMP - Dewi Roro Ireng; Septi Zakiah Rahmania; Mimin Sahmini (IKIP Siliwangi, 2019)
This research is motivated by a lot of student writing that does not fit into the structure of the text of a fantasy story due to several factors that make it difficult for students to pour their writing. In this research, formulate a way to make student writing in making fantasy story text according to its structure? The purpose of this study was to describe fantasy stories based on agreed structure, complications and resolution. Get acquainted with junior high school students in writing fantasy story texts according to the structure and language of fantasy stories. Therefore, this study focuses more on the results of student skills, for the analysis of each of the results of his writing to fit the text structure of fantasy stories. The method used in this research is descriptive qualitative. The instrument in this study is about texts that write fantasy stories to students. Analysis of the data in this study includes the results of the study that were approved by two assessors namely assessor 1 and assessor 2 responded by calculating the average results of student writing. With the subject of research successful students 22 people. The value of the results of this study of 3 fantasy story text structure of the discussion, complications and maximum approval of 8.75, an average value of 75 and a minimum value of 50. These results show how the ability of students in writing fantasy story text is sufficiently in accordance with the demand for text structure fantasy story.